Case of placental insufficiency and premature delivery in a Fontan pregnancy: physiological insights and considerations on risk stratification. Issue 1 (19th February 2021) - Ordoñez, Maria Victoria; Biglino, Giovanni; Caputo, Massimo; Kelly, Brenda; Mohan, Aarthi; Trinder, Johanna; Curtis, Stephanie L
Abstract : Objectives: The coexistence of two complex physiologies such as Fontan and pregnancy is still not fully understood. We aim to add a unique and essential knowledge to help our colleagues in the management of Fontan patients that undergo pregnancy as well as the fetus and the placenta perfusion. Methods and results: We analyse the coexistence of Fontan and pregnancy physiology on a complex case of a woman with hypoplastic left heart syndrome palliated with a univentricular repair who became pregnant, delivered very prematurely and had atypical placental findings. Conclusion: Histopathological analysis of the placenta could help us to refine the understanding of Fontan physiology adaptation during pregnancy, predict women and fetal outcomes as well as to plan a better pre-pregnancy status. However, further evidence is needed in order to reach a more solid and unified conclusion.